State Intervention on the Housing Market - a Few Remarks on the Commercialization of Social Housing - Suszyńska, Katarzyna (Studia Oeconomica Posnaniensia, 2017)
Until recently, state intervention and the "invisible hand of the market" were perceived as antagonistic notions, yet today they appear to be acting as complementary mechanisms. Currently, most European governments support the development of the social housing market not only through own state-driven housing programs, but also by promoting and subsidizing market mechanisms. An increasingly popular solution among European countries is the use of commercial housing stock and market techniques to solve the housing problems of destitute households. The commercialization of public tasks within housing does not mean, however, that the state can withdraw completely from regulating it. In the paper, factors which justify state intervention in the sphere of housing are explored, as well as the objectives and the consequences of such actions. The author also presents new trends in the market regulation of social housing, and discusses the shape of state intervention on the relevant area in the future.